"We need to protect each other": COVID-19 vaccination intentions and concerns among Racialized minority and Indigenous Peoples in Canada. (November 2022) - Manca, Terra; Humble, Robin M.; Aylsworth, Laura; Cha, Eunah; Wilson, Sarah E.; Meyer, Samantha B.; Greyson, Devon; Sadarangani, Manish; Parsons Leigh, Jeanna; MacDonald, Shannon E.
Abstract: People may choose to receive vaccines in response to pressures that outweigh any concerns that they have. We explored Racialized minority and Indigenous Peoples' motivations for, perceptions of choice in, and concerns about, COVID-19 vaccination. We used a sequential explanatory mixed methods approach, including a national survey administered around the time vaccines were first authorized (Dec 2020) followed by qualitative interviews when vaccines were becoming more readily available to adults (May–June 2021). We analyzed survey data using descriptive statistics and interviews using critical feminist methodologies. Survey respondents self-identified as a Racialized minority (n = 1488) or Indigenous (n = 342), of which 71.4% and 64.6%, respectively, intended to receive a COVID-19 vaccine. Quantitative results indicated perceptions of COVID-19 disease were associated with vaccination intention. For instance, intention was associated with agreement that COVID-19 disease is severe, risk of becoming sick is great, COVID-19 vaccination is necessary, and vaccines available in Canada will be safe (p < 0.001). COVID-19 vaccines were in short supply in Canada when we subsequently completed qualitative interviews with a subset of Racialized minority (n = 17) and Indigenous (n = 10) survey respondents. We coded interview transcripts around three emergent themes relating to governmentality and cultural approaches to intersectional risk theories: feelings of collective responsibility, choice as privilege, and remaining uncertainties about COVID-19 vaccines. For example, some mentioned the responsibility and privilege to receive a vaccine earlier than those living outside of Canada. Some felt constraints on their freedom to choose to receive or refuse a vaccine from intersecting oppressions or their health status. Although all participants intended to get vaccinated, many mentioned uncertainties about the safety and effectiveness of COVID-19 vaccination. Survey respondents and interview participants demonstrated nuanced associations of vaccine acceptance and hesitancy shaped by perspectives of vaccine-related risks, symbolic associations of vaccines with hope, and intersecting social privileges and inequities (including racialization). Highlights: Mixed methods exploration of social privileges and inequities in vaccine intentions. Explored acceptance of new COVID-19 vaccines instead of framing refusal as abnormal. Theoretical insights into vaccines from intersectional approaches to risk governance. Practical need to support those intending to be vaccinated despite uncertainties.